The petrophysical analysis and evaluation of hydrocarbon potential of sandstone units in the Bredasdorp Central Basin - Olajide, Oluseyi (University of the Western Cape, 2013)
Magister Scientiae - MSc === This research was aimed at employing the broad use of petrophysical analysis and reservoir modelling techniques to explore the petroleum resources in the sandstone units of deep marine play in the Bredasdorp Basin. === South Africa